PENGARUH CUSTOMER PERCEPTION TERHADAP MINAT BELI KONSUMEN MELALUI MULTIATTRIBUTE ATTITUDE MODEL PADA PRODUK HOTWAY'S CHICKEN - Syaifudin Maarif; Esti Maulida Apriliana; Nafi Mardiansyah; Zidny Camelia; Muhafidhah Novie (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the influence of consumer perception on purchase intention through the Multiattribute Attitude Model on Hotway's Chicken products. The research method used is quantitative with a descriptive and analytical approach using the PLS-SEM technique. Primary data was collected through questionnaires from 120 respondents selected by accidental sampling technique. The results of the analysis show that consumer perception has a significant effect on the Multiattribute Attitude Model, which in turn also has a significant effect on consumer purchase intention. In addition, consumer perception also has a direct effect on product purchase intention. With an R-square value on purchase intention of (38.7%), this study confirms that increasing consumer perception and positive attitudes can encourage purchase interest in Hotway's Chicken products. This finding provides important implications for product attribute management and marketing strategies to increase sales.